THU0678 Trend of venous thromboembolism among select rheumtologic diseases: an audit of large national us database. (12th June 2018) - Poudel, D.R.; Dhital, R.; Paudel, P.; Basnet, S.; Sharma, P.; Shrestha, P.; Karmacharya, P.
Abstract : Background: Venous thromboembolism (VTE) is 3rd commonest cause of cardiovascular deaths and encompasses deep-venous thrombosis (DVT) and pulmonary embolism (PE). Rheumatologic diseases have been found to be associated with an increased risk of VTE among hospitalised patients. Objectives: To describe the trend of VTE among select rheumatologic diseases over 15 years. Methods: We used National Inpatient Sample (NIS) database for years 2000–2014 to identify adults≥18 years with select rheumatologic diseases and VTE based on ICD-9 codes. Prevalence was age-sex adjusted against US census population data. STATA was used for querying database and Joinpoint regression was used to analyse annual trends of prevalence in terms of annual percentage change (APC). Logistic regression with survey command was used to derive adjusted odds of VTE association for all years combined. Results: We included a total of 461, 089, 203 hospitalizations among which 8, 822, 456 (1.91%) had VTE (table 1). An upward trend in the prevalence of VTE (APCs 2.45–4.16) (and PE subset) was noted in most of the rheumatologic disease groups (figure 1). DVT, however, had a decreasing or non-significant increasing trend among most disease groups (data for DVT and PE not shown). The adjusted odds of VTE association was highest among SLE group (aOR=2.2, CI=2.17–2.3) followed by DM/PM (aOR=2.0, CI=1.9–2.2) (table 1). Table 1 Frequency counts of rheumatologic diseases and controls; prevalence of VTE and adjusted regression analysis of VTE association Conclusions: Inflammatory rheumatologic diseases seem to be associated with higher prevalence and odds of having VTE among hospitalised patients and the overall trend is rising. This might indicate some lag in following of guidelines for VTE prophylaxis. Closer look into the implications of stricter prophylaxis among rheumatologic patients is a matter of further studies. Disclosure of Interest: None declared